Influence of oxygen flow on crystallization and morphology of LiNbO 3 thin films - Simões, A. Z. [UNESP]; Gonzalez, A. H. [UNESP]; Zaghete, M. A. [UNESP]; Stojanovic, B. D. [UNESP]; Cavalheiro, A. A. [UNESP]; Moeckli, P.; Setter, N.; Varela, José Arana [UNESP] (My University, 2002)
Polymeric precursor solution (Pechini method) was used to deposit LiNbO 3 thin films by spin-coating on (100) silicon substrates. X-ray diffraction data of thin films showed that the increase of oxygen flow promotes a preferred orientation of (001) LiNbO 3 planes parallel to the substrate surface. Surface roughness and grain size, observed by atomic force microscopy, change also with oxygen flow. © 2002 Taylor & Francis.
Keywords: Crystallization; LiNbO 3; Rietveld analysis; LiNbO3; Oxygen flow; Substrate surface; Atomic force microscopy; Crystalline materials; Flow of fluids; Lithium niobate; Morphology; Oxygen; Silicon; Spin coating; Thin films